Optimization of Gold Thin Films Thicknesses in Enhancing SPR Response - Murat, NF; Mukhtar, WM; Rashid, ARA; Dasuki, KA; Yussuf, AARA (IEEE, 2024)
Nowadays, surface plasmon resonance (SPR) sensor has been widely used in biosensing applications to detect the wide diversity of biomolecular interactions. There are few parameters need to be concerned in order to optimize the performance of SPR sensors such as film thicknesses, type of thin films and their configurations. In this study, we seek to determine the optimum thicknesses of hybrid thin films which consist of gold-graphene oxide layers for the enhancement of SPR sensor sensitivity. By using a theoretical approach, a WINSPALL 3.02 simulator had been used to investigate the effects of various thicknesses of hybrid configuration's thin films towards the excitation of surface plasmon polaritons (SPP). A layer of 3 nm protein was added to compare the maximum adsorption of the SPR sensor based on their configuration. It was found that the optimum thicknesses of gold and graphene oxide are 50 nm and 0.68 nm respectively for achieving best sensitivity. Thus, the sensitivity value for gold-GO thin films is higher than silver-GO which are 19.42 degrees/RIU and 5.45 degrees/RIU with FWHM = 2.28 degrees and 0.64 degrees respectively.